Plasma guns of an erosion type with the pulse-periodic gas-metal injection - Vinnikov, D.V.; Katrechko, V.V.; Yuferov, V.B.; Tkachev, V.I. (Problems of Atomic Science and Technology, 2022)
The design of the modular plasma guns of an erosion type that operate in the pulse-periodic mode has been described. The injection of the electrode and dielectric materials occurs due to the combination of many processes initiated by the high-voltage surface discharge. The guns with the dielectrics of (C₂H₄)n and (C₂F₄)n types have been compared. Optical spectrograms of discharges for a (C₂F₄)n dielectric have been obtained. The radial and axial spread of sprayed components that are the part of plasma guns has been specified and the composition of the sediments deposited on the targets has been defined.